The opposite duality and its impact on textual consistency in the poetry of Hamid Al-Rawi: (He is not Kohl) as a model - Shakir, Eather (Al-Adab Journal, 2023)
The problem of the study and its hypothesis revolves around highlighting the aesthetics of contradiction and bilateral relations and their impact on textual consistency and its function in contemporary poetry and the connotations that emerge from it, and its importance is gained from this study being an applied study on the poetry of the poet Professor Hamid Al-Rawi and revealing the extent of his intention in employing this art in his texts and the connotations that he aims at. The purpose of the research is to shed light on contemporary Iraqi poetry and research in what carries this poetry of creativity and potential and rhetorical arts and linguistic richness reflects the extent of the sobriety of the poet stemming from it, and this topic was one of the important aspects of those arts Almrssa in the poetry of poets of the contemporary era, which the modern poet in employing them in his poems within the modernization of the form of the poem and its content.